Macrophage fatty acid oxidation inhibits atherosclerosis progression. (February 2019) - Nomura, Mitsunori; Liu, Jie; Yu, Zu-Xi; Yamazaki, Tomoko; Yan, Ye; Kawagishi, Hiroyuki; Rovira, Ilsa I.; Liu, Chengyu; Wolfgang, Michael J.; Mukouyama, Yoh-suke; Finkel, Toren
Abstract: Atherosclerosis is a chronic disorder of the vessel wall. One key regulator of disease progression is lipid handling in macrophages. However, the role of macrophage mitochondrial-dependent fatty acid β-oxidation (FAO) in atherosclerosis is not well defined. To address this, we focused on carnitine palmitoyltransferase (CPT) 1 and 2, which play an essential role in the transport of long chain fatty acids (FAs) into the mitochondria. Using conditional alleles of these mitochondrial enzymes, we have generated myeloid-specific Cpt1a and Cpt2 knockout mutants (CPT1a M-KO and CPT2 M-KO). In culture, macrophages derived from CPT1a and CPT2 M-KO mice have impaired FAO, enhanced expression of the CD36 scavenger receptor, increased uptake of oxidized low-density lipoprotein (oxLDL), and augmented transformation into cholesterol-rich foam cells. In line with these in vitro observations, in the atherosclerosis-susceptible apolipoprotein E (ApoE) KO background, CPT2 M-KO mice demonstrated augmented atherosclerosis, accompanied by increased accumulation of aortic macrophages with elevated CD36 expression. These data suggest that macrophage FAO is athero-protective and that augmenting FAO may potentially slow atherosclerotic progression.